In the Permanent Collection - Wortman, Stefanie (Book collections on Project MUSE., 2014)
Trying to make sense of a disordered world, Stefanie Wortman's debut collection examines works of art as varied as casts of antique sculpture, 19th-century novels, and even scenes from reality television to investigate the versions of order that they offer. These deft poems yield moments of surprising levity even as they mount a sharp critique of human folly.